2009
DOI: 10.1159/000240162
|View full text |Cite
|
Sign up to set email alerts
|

Severe Micrognathia: Indications for EXIT-to-Airway

Abstract: The ex utero intrapartum treatment (EXIT) procedure has become an important management option in cases of fetal airway obstruction. Select cases of severe micrognathia may be candidates for EXIT-to-Airway due to high-risk of airway obstruction at birth. Here we present three successful EXIT-to-Airway procedures for the management of congenital micrognathia in its most severe manifestations. Case 1: A 23-year-old G3P1011 with a pregnancy complicated by severe micorgnathia, jaw index <5th percentile, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…The EXIT procedure has since been applied to other conditions in which advanced perinatal resuscitation is required. It is being used for controlled airway access in fetuses with large neck masses [2,3 && ], congenital high airway obstruction [4][5][6] or severe micrognathia (EXIT for airway) [7], as a bridge for fetuses with anticipated immediate need for extracorporeal support (EXIT-to-ECMO) [8,9], or for resection of large intrathoracic masses that may impair fetal resuscitation (EXIT-to-resection) [10,11 & ]. This article reviews indications, technique and outcomes following EXIT procedure for fetal neck masses.…”
Section: Introductionmentioning
confidence: 99%
“…The EXIT procedure has since been applied to other conditions in which advanced perinatal resuscitation is required. It is being used for controlled airway access in fetuses with large neck masses [2,3 && ], congenital high airway obstruction [4][5][6] or severe micrognathia (EXIT for airway) [7], as a bridge for fetuses with anticipated immediate need for extracorporeal support (EXIT-to-ECMO) [8,9], or for resection of large intrathoracic masses that may impair fetal resuscitation (EXIT-to-resection) [10,11 & ]. This article reviews indications, technique and outcomes following EXIT procedure for fetal neck masses.…”
Section: Introductionmentioning
confidence: 99%
“…Time, proficiency, and familiarity with the EXIT procedure have led to the expansion of its applications 1. Based on a series of three patients, Morris et al have suggested that micrognathic infants with a jaw index <5 percentile and evidence of aerodigestive tract obstruction are indications for performing an EXIT procedure 2, 3. In an effort to further our knowledge regarding prenatal counseling for optimal and appropriate airway management of micrognathic fetuses, this study examines the rate of airway intervention within the first 24 hours of life in 123 newborns with micrognathia, and identifies prenatal characteristics that represent risk factors for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Bu hastaların erken bulgusu, USG esnasında saptanan polihidramniyostur. Hastaların doğum sonrası erken entübasyonunun riskli olduğu durumlarda EXIT prosedürü uygulanmaktadır.…”
Section: Havayolu Tikanikliklariunclassified